2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090309
|View full text |Cite
|
Sign up to set email alerts
|

Improving impaired balance function: Real-time versus carry-over effects of prosthetic feedback

Abstract: This study investigated whether training with realtime prosthetic biofeedback (BF) of trunk sway induces a carry-over improvement in balance control once BF is removed. 12 healthy older adults and 7 uncompensated unilateral vestibular loss patients were tested. All participants performed a battery of 14 balance and gait tasks (pre-test) upon their initial lab visit during which trunk angular sway was measured at L1-3. They then received balance BF training on a subset of 7 tasks, three times per week, for two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 18 publications
3
26
1
Order By: Relevance
“…Our data has shown that the amount of the post-therapeutic changes is proportional to the degree of vestibular loss, patients with profound deficits benefiting more from this therapy than those with unilateral losses. This is in line with previously reported findings showing that body swaybased auditory [18,19] and multi-modal [20] biofeedback have a greater stabilizing effect in vestibular patients than in healthy subjects.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our data has shown that the amount of the post-therapeutic changes is proportional to the degree of vestibular loss, patients with profound deficits benefiting more from this therapy than those with unilateral losses. This is in line with previously reported findings showing that body swaybased auditory [18,19] and multi-modal [20] biofeedback have a greater stabilizing effect in vestibular patients than in healthy subjects.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, analysis of the therapy effect in posturographic scores revealed similarities with those observed in patients wearing auditory [2,3,18,19,24,25], vibrotactile [6,21,25,26] or multi-modal [20,22] biofeedback devices providing a real-time postural signal. Our patients, however, were tested without feedback, 4 h after the last use of the BrainPort balance device.…”
Section: Discussionsupporting
confidence: 69%
“…We assume that long-term training would have reduced the feedback thresholds to values of HCs as BVL values would be individually reset to lower values following reassessment with no feedback. Lower no feedback values would be achieved via a carry-over effect of the feedback to the no feedback condition [3]. …”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, a number of investigators have developed balance prostheses to provide persons with balance problems a replacement for vestibular sensory information on body sway. Such prosthetic systems generally rely on vibrotactile or auditory feedback or both modes, appropriately coded with body sway information [3-9]. There are variations concerning where the sway measures are taken, and how the sway signals are processed, and at which body location the feedback is provided.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation